IMPROVE OF “UZBEK INDEX OF PREMATURE EJACULATION - Azamjon Makhmudov (Web of Journals Publishing, 2025)
A questionnaire developed to test the “Uzbek Premature Ejaculation Index”. The main goal is to exclude the gray zone (13-16 points) from the scoring system of the Uzbek Index of Premature Ejaculation. The study was conducted from October 2020 to April 2023 at the Republican Specialized Scientific and Practical Medical Center of Urology in partnership with the Department of Urology of the Tashkent Medical Academy. In our study, 200 male patients aged 20 to 50 years who had been in a stable sexual relationship for at least six months completed the Uzbek Index of Premature Ejaculation Questionnaire. They were monogamous. A group of 30 patients, each with a score between 13 and 16, was randomly assigned to the UIPE Questionnaire, which was filled out by 200 male patients who had experienced premature ejaculation. Other accompanying illnesses were examined and treated for them. The treatment control group was prompted to complete the questionnaire. Treatment-free patients with concomitant diseases who scored 13 in the control group demonstrated a significant increase in IELT. The IELT of patients with 14 16 scores showed no change. Despite the fact that a 13 score is not indicative of PE, it can be used to treat concurrent diseases and alleviate symptoms of early childhood illness. It has been determined that a score of 13 or higher is not diagnosticable in PE and should not be sought through further diagnosis. “Uzbek Index of Premature Ejaculation” is the validated measure for outcomes measured by the patient.
Keywords: Uzbek index of premature ejaculation (UIPE), Premature ejaculation (PE), Premature Ejaculation Diagnostic Tool (PEDT), Intra-vaginal ejaculatory latency time (IELT).